1980
DOI: 10.1111/j.1469-8749.1980.tb03711.x
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Jaundiced Infants undergoing Phototherapy

Abstract: SUMMARY Ten full‐term jaundiced infants were examined with the Brazelton Scale before, during and following phototherapy. They were compared with 10 non‐jaundiced control infants examined at the same post‐partum ages. All infants were appropriate for gestational age and free of perinatal complications other than hyperbilirubinemia. Differences on the orienting items of the Brazelton examinations (primarily visual orienting) were found prior to the onset of phototherapy or separation, and persisted for the leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Phototherapy is widely accepted as a standard method for the management of neonatal hyperbilirubinaemia and has minimal adverse effects (4–13). The American Academy of Pediatrics Subcommittee for Hyperbilirubinaemia left the decision of discontinuing phototherapy at the discretion of the physicians, depending ‘on the age at which the phototherapy is initiated and the cause of hyperbilirubinaemia’.…”
Section: Discussionmentioning
confidence: 99%
“…Phototherapy is widely accepted as a standard method for the management of neonatal hyperbilirubinaemia and has minimal adverse effects (4–13). The American Academy of Pediatrics Subcommittee for Hyperbilirubinaemia left the decision of discontinuing phototherapy at the discretion of the physicians, depending ‘on the age at which the phototherapy is initiated and the cause of hyperbilirubinaemia’.…”
Section: Discussionmentioning
confidence: 99%
“…Phototherapy is useful for the acute management of neonatal hyperbilirubinemia, although some studies reported possible adverse effects. [32][33][34][35][36][37][38][39] The suggestion that photometabolic products might interfere with albumin binding of bilirubin raised the possibility that phototherapy might contribute to the neurotoxicity of bilirubin. 52 There was the possibility of delayed effects of phototherapy concerning neurodevelopment, [32][33][34][35][36] vision, 37 and skin abnormalities.…”
Section: Phototherapy In Neonatal Hyperbilirubinemiamentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] The suggestion that photometabolic products might interfere with albumin binding of bilirubin raised the possibility that phototherapy might contribute to the neurotoxicity of bilirubin. 52 There was the possibility of delayed effects of phototherapy concerning neurodevelopment, [32][33][34][35][36] vision, 37 and skin abnormalities. 38,39 However, recent studies, 40,52 including a multicenter randomized controlled study, 40 concluded that phototherapy effectively controlled neonatal hyperbilirubinemia without adverse outcome at 6 years and was at least as effective as exchange transfusion alone.…”
Section: Phototherapy In Neonatal Hyperbilirubinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of these studies did not account for or report body weight changes, a well‐known risk factor for OA. ( 13–15 ) On the other hand, a more recent meta‐analysis did not support the idea that diabetes is an independent risk factor for OA and suggested that an increase in body weight, an effect found more often in T2DM patients, is the main driver of OA in this population. ( 11 ) Few additional studies are also in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 97%